Home health care delivery problem - GUNAWAN, Aldy (Institutional Knowledge at Singapore Management University, 2017)
We address the Home Health Care Delivery Problem (HHCDP), which is concerned with staff scheduling in the home health care industry. The goal is to schedule health care providers to serve patients at their homes that maximizes the total collected preference scores from visited patients subject to several constraints, such as workload of the health care providers, time budget for each provider and so on. The complexity lies in the possibility of cancellation of patient bookings dynamically, and the generated schedule should attempt to patients’ preferred time windows. To cater to these requirements, we model the preference score as a step function which depends on the arrival time of the visit and the resulting problem as the Team Orienteering Problem (TOP) with soft Time Windows and Variable Profits. We propose a fast algorithm, Iterated Local Search (ILS), which has been widely used to solve other variants of the Orienteering Problem (OP). We first solve the modified benchmark Team OP with Time Window instances followed by randomly generated instances. We conclude that ILS is able to provide good solutions within reasonable computational times.